Study on Management of Diabetic Foot Ulcer in a Rural Tertiary Care Hospital - A. Arshia Fathima; Ananya Sarvotham; Milind Iddalagi (Indian Journal of Vascular and Endovascular Surgery, 2024)
Background: Diabetic foot ulcer is a common complication among diabetic patients. Diabetes is prone to multiple complications related to microvascular, macrovascular, and metabolic etiologies. Diabetic foot ulcers can ultimately lead to infection, gangrene, amputation, and even death. Methods: This is a prospective observational study, that was carried out on 100 adult patients between July 2022 and January 2023 diagnosed with diabetic foot ulcer, treated at MVJ Medical College and Research Hospital. Inclusion criteria were all patients aged above 18 years. Exclusion criteria were patients with peripheral vascular disease not arising due to diabetes, patients with varicose veins, and patients who are undergoing chemotherapy or immunocompromised and in sepsis. Routine blood investigation, blood sugar levels, and liver function test were done. Specific investigation including discharge from wound/biopsy for culture, urine routine, x- ray of foot and doppler studies was done. The patient underwent standard surgical procedure and was followed up. The collected data were analyzed using SPSS-21 software. Results: The data collected were analyzed and documented. In our study, we noted that male cases were about 64% and female cases were about 36%, and the ratio of male:female is 1.7. The maximum number of cases were observed in the age group of more than 65 years, and the most common site of involvement was right foot. Conservative treatment involved diabetes control with drugs and insulin followed by wound management by dressing, debridement, amputation, and split skin grafts. Conclusion: Foot ulcer is preventable, and relatively simple interventions can reduce the risk of amputations by 80%. Management is primarily concerned about wound healing, and stopping the spread of infection, this is achieved by various methods such as split skin grafting, amputations, and conservative methods like dressing.